Effects of ultrasonic impact treatment on weld microstructure, hardness, and residual stress. Issue 14 (22nd September 2017) - Liu, Chuan; Chen, Dongjun; Hill, Michael R.; Tran, Minh N.; Zou, Jiasheng
ABSTRACT: Layered ultrasonic impact treatment (LUIT) was used on V-groove welds in 55 mm Q345 steel plate. Two welds were prepared, one by conventional gas metal arc welding (GMAW) and the other by GMAW and LUIT, where impact treatment was performed at nine stages during filling of the 28-pass weld. Microstructure, hardness, and residual stress in the welds were compared. While residual stress is very similar, there are significant differences in microstructure and hardness. The LUIT weld has mainly equiaxed grains and uniform hardness, while the conventional weld has columnar grains and a hardness gradient. It appears that beads in the LUIT weld did not exhibit columnar grain growth, and instead equiaxed grains grew from the fusion boundary into the weld.